(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Gastronomic tourism has increasingly attracted scholarly attention as a meaningful form of cultural and experiential travel. This paper explores gastronomic tourism terminology through a comparative examination of English and Uzbek languages. The primary objective of the study is to analyze core terminological units, identify their semantic properties, and examine how linguistic and cultural factors influence their usage. The research employs qualitative methods, including descriptive and comparative analysis. The findings suggest that English gastronomic tourism terminology demonstrates a high level of international standardization, whereas Uzbek terminology remains closely tied to national culinary traditions and cultural values. The study contributes to tourism linguistics and intercultural communication by highlighting terminological variation across languages.